Genomic surveillance reveals multiple introductions of SARS-CoV-2 into Northern California - Deng, Xianding; Gu, Wei; Federman, Scot; du Plessis, Louis; Pybus, Oliver G; Faria, Nuno R; Wang, Candace; Yu, Guixia; Bushnell, Brian; Pan, Chao-Yang; Guevara, Hugo; Sotomayor-Gonzalez, Alicia; et al. (Science (American Association for the Advancement of Science), 2020)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread globally, with >365,000 cases in California as of 17 July 2020. We investigated the genomic epidemiology of SARS-CoV-2 in Northern California from late January to mid-March 2020, using samples from 36 patients spanning nine counties and the Grand Princess cruise ship. Phylogenetic analyses revealed the cryptic introduction of at least seven different SARS-CoV-2 lineages into California, including epidemic WA1 strains associated with Washington state, with lack of a predominant lineage and limited transmission among communities. Lineages associated with outbreak clusters in two counties were defined by a single base substitution in the viral genome. These findings support contact tracing, social distancing, and travel restrictions to contain the spread of SARS-CoV-2 in California and other states.